Educational institution reform: Insights from the complexity-intelligence strategy - NG, Pak Tee (Institutional Knowledge at Singapore Management University, 2010)
This paper attempts to draw some significant insights for educational institution reform from the paradigm of organizing around intelligence. Using the Complexity-Intelligence strategy, human organizations are visualized as intelligent beings possessing an orgmind with high collective intelligence, and other intelligence-related characteristics that are commonly found in highly intelligent biological beings including consciousness, complex adaptive dynamic, autopoiesis, self-organization, learning, adaptation and emergence. Such intelligent human organizations primarily focus on quality connection, optimizing the intrinsic intelligence sources, and nurturing a high level of collective intelligence. It is a living intelligence-centric world. In this study, four insights and their implications from the Complexity-Intelligence strategy that are applicable to education organizations, namely embracing complexity and nonlinearity, enhancing connectivity, developing individual mindfulness and orgmindfulness, and capitalizing on all sources of intense intelligence (human thinking systems) are analyzed. The result of this analysis reveals fresh and significant information and applications for all educational institutions that aspire to enhance their collective intelligence, adaptive capacity and standard of learning in a new intelligence era.